Teaching Vocabulary Using Teaching Aids At Elementary School In SDN Gumpang 3 Kartasura: An Experimental Research - Wulansari, Diah (2004)
Teaching vocabulary at Elementary School is to introduce simple English words. The objective of this research is to describe what are the procedures, the results, the advantages and the disadvantages of teaching vocabulary using teaching aids. The materials of this research have some fields, such as: the first material, the writer gives about numbers and colors, the second material are fruits and vegetables, the third material are animals and the fourth material are things around the house. In this research, the writer carries out experiment. The writer takes 24 students as population. The writer takes all the population as sample because the subject is less than one hundred. To know the result of teaching vocabulary, the writer gives wo kinds of test, namely: pre-test and post-test. Each test consists of 30 test items. In pre-test, the highest score is 96, the lowest score is 35, and it's average score is 70,41. While in post-test, the highest score is 100, and the lowest score is 53, and it's average score is 84,08. From the two tests the writer compares to know how far the students can achieve the target vocabulary by using teaching aids. Finally, the writer concludes that by using teaching aids in teaching English vocabulary the students can achieve the target vocabulary well.